A Conceptual Model Development For Persuasive E-Wom Reviews: Challenges And Future Prospect - et. al., Najah Mohammed ALRasheedi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aims to extend the body of knowledge on eWOM reviews by understanding the determinants of persuasive eWOM review and their effect on tourists' attitude toward the destination abroad and travel intention. This study tries to identify critical factors that influence users' attitudes and intentions when processing a persuasive eWOM review. Past literature on eWOM, Persuasive eWOM, Travel Intention, Elaboration likelihood model (ELM)Theory of Planned Behaviour (TPB) and Trust Transfer theory was extensively reviewed to develop a conceptual model. The current study has developed several prepositions by linking the variables for the future prospect. This study contributes to understanding what factors come into play to determine potential tourists' trust in a reviewer and their acceptance, which has an important role in developing travel intention. Concerning TPB, the study further contributes by improving the theory of planned behaviour's predictive ability and explanatory power. This study extends the theory of planned behaviour by including the information acceptance construct and utilising the extended model to explain the influence of information acceptance on travel intention. To the best of the current study’s author knowledge, there is no such study has been conducted before.